PELATIHAN PENGUNAAN ARTIFICIAL INTELLIGENCE DALAM PEMBUATAN SOAL MULTIPLE CHOISE MENGGUNAKAN STORYLINE - Aman, Mustar; iskandar, Joni; Sasono, Ipang; Riyanto; Wiyono, Nuri; Suroso; Widodo, Adi; Agung nugroho, Yunianto; yanto, Adi; Maria setyastanto, Albertus (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2024)
The use of Information Technology (IT) in education has brought about significant transformation, enabling innovation in learning. This article discusses the positive impact on the quality of learning in vocational high schools. Practical steps, such as visits, identification, socialization, training using AI, especially storyline3 to compile multiple-choice questions in learning, were implemented by involving several vocational high school teachers in Tigaraksa-Tangerang. The evaluation showed an increase in participants' understanding and enthusiasm for the use of storyline3 in designing multiple-choice questions in practice and exams. The results show that the use of artificial intelligence, such as storyline 3, can be an effective tool to improve the quality of learning at the vocational level.